The Impact of Indonesian Banks' Mergers and Acquisitions on Performance and Market Power - Tanubrata, Kezia Jovita; Noveria, Ana (Journal of Economics and Business UBS, 2025)
This study aims to analyze the impact of mergers and acquisitions (M&A) carried out by banks in Indonesia on market performance and strength. The wave of banking consolidation that occurred in Indonesia was driven by the encouragement from regulators to strengthen the resilience of the banking sector in Indonesia as well as the strategic goals of banks to increase their competitiveness. This study uses the staggered Difference-in-Differences (DiD) method developed by Callaway and Sant'Anna (2021), which allows comparisons between banks that have merged (treated) and banks that have not merged (control) in various different time periods. Using panel data taken from the Financial Services Authority (OJK) report for the 2017-2022 period, this study uses the variables Net Interest Margin (NIM) and Return on Equity (ROE) as indicators of profitability, BOPO as an indicator of efficiency, and the Lerner Index to measure market strength. Empirical results show that the impact of M&A on bank profitability and efficiency is heterogeneous between banks. Some banks have proven to be more efficient and more profitable after M&A, while others have experienced a decline in short-term profitability due to high integration costs and operational challenges. Nevertheless, the regression results show a consistent positive effect on market strength across the observed banks. These findings indicate that banks gain greater ability to price above marginal costs after M&A, in line with market power theory.